Analysis of Financial Statements Based on Financial Accounting Standards Financial Accounting Standards of Entities without Public Accountability at KPRI Ringgit Kec. Kendit Kab. Situbondo - Nur Da'iyah Hasanah; Rendy Mirwan Aspirandi; Riyanto Setiawan Suharsono (West Science Accounting and Finance, 2024)
The purpose of this study was to determine and analyze how to prepare financial statements at KPRI Ringgit Kec. Kendit Kab. Situbondo and to determine the application of SAK ETAP to the financial statements of KPRI Ringgit Kec. Kendit Kab. Situbondo. This research method is to use qualitative methods in the form of interview results, retrieval of financial statement data in 2022 and documentation. The analysis technique used is conducting a survey by interviewing, collecting data, namely transaction evidence and financial statements for the 2022 period obtained through interviews, presenting KPRI Ringgit's financial statements, analyzing financial statements in accordance with SAK ETAP, namely balance sheets, statements of results of operations, statements of changes in equity, cash flow statements, and notes to financial statements, and drawing conclusions from the results of the research conducted. The results showed that the preparation of the financial statements of KPRI Ringgit Kendit District is not in accordance with SAK ETAP, which only consists of a statement of financial position, calculation of results of operations and a statement of changes in equity. Meanwhile, according to SAK ETAP the financial statements consist of a statement of financial position, income statement, cash flow statement, statement of changes in equity, and notes to financial statements.